منهاج الإسلام لمناهضة خطاب الكراهية: دراسة تحليلية - إسماعيل، أردوان مصطفي; عارف، عارف علي (جامعة صلاح الدين, 2020)
لقد أمسى موضوع خطاب الكراهية من موضوعات العصر، وهو خطاب يزرع الكراهية بين الأديان، والتنافر بين شعوب العالم، وثقافات الأمم. ومن هنا، فإن البحث سعى إلى استجلاء المنهجية الإسلامية لمناهضة خطاب الكراهية. وقد جلى البحث الأسباب المفضية إلى نشوء خطاب الكراهية، من أبرزها: الجهل بالعلوم الشرعية وإساءة فهمها، والغلو والتطرف، والتعصب. كذلك، أبان البحث منهاج الإسلام لمعالجة خطاب الكراهية وذلك بتنشيط المنهج الوسطى، وتفعيل الأخلاقيات الإسلامية في حياة المسلمين. وقد خلص البحث إلى أن الإسلام كتاباً وسنة حرم خطاب الكراهية، وأمر المسلمين بتقديم القول الحسن والأحسن إلى الناس كافة. وأوصى المؤسسات الدينية، في العالم، بالسعي من أجل تعميق الخطاب الأحسن، وقول الآخر.
The subject of hate speech has become a huge issue nowadays, and it is a discourse that cultivates hatred between religions, the incompatibility between the peoples of the world and the cultures of nations. Hence, the research sought to clarify the Islamic methodology to combat hate speech. The research made clear the reasons leading to the emergence of hate speech, the most prominent are: ignorance of the Islamic sciences, exaggeration and extremism. Likewise, the research demonstrated the approach of Islam to address hate speech by stimulating the moderate approach and adherence to Islamic ethics in the field of words and deeds. The research concluded that Islam forbade hate speech, and directed Muslims to present the good speech and the best one to all people. It is recommended that religious institutions, in the world, to strive to deepen the better discourse and accept the other.
Keywords: خطاب الكراهية -- القيم الإسلامية -- التواصل الشفهي -- العلوم الشرعية